Price Responsiveness and Market Conditions - Braulke, Michael (Econometrica, 1983)
Edlefsen [3] has shown that a phenomenon of great similarity to the strong LeChatelier principle can be established when altering the feasible set of an optimizing agent by suitably replacing existing constraints rather than adding new ones. Here it was demonstrated that essentially the same phenomenon occurs when altering the objective function in a systematic manner rather than the.feasible set. The result obtained is general enough to allow a replication of Edlefsen's analysis of a household choosing between quantity and quality when facing hedonic prices, and served here furthermore in an application to the theory of the firm where it was demonstrated that a systematic relationship exists between the intensity of the reactions of a producer to changes in a conjugate parameter and the conditions prevailing in his markets.